2018
DOI: 10.1038/s41386-018-0149-y
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine in the oval bed nucleus of the stria terminalis contributes to compulsive responding for sucrose in rats

Abstract: Binge eating disorder (BED) is characterized by periods of excessive food intake combined with subjective feelings of loss of control. We examined whether sucrose bingeing itself leads to uncontrolled or compulsive responding and whether this effect is magnified following a period of abstinence. We then assessed dopamine (DA) modulation of inhibitory synaptic transmission in the oval bed nucleus of the stria terminalis (ovBNST) as a neural correlate of compulsive responding and whether this behavioral effect c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…In sum, rodent models of sucrose bingeing provide valuable insight into the behavioural and biological underpinnings of maladaptive eating. Restricting access to palatable food increases the propensity to binge, leading to alterations in reward processing (Smail-Crevier et al, 2018) as well as neurophysiological changes associated with compulsive responding (Maracle et al, 2018). We now identify a contribution of MORs to binge eating, findings that may translate to clinical treatment (Ziauddeen et al, 2013).…”
Section: Discussionmentioning
confidence: 75%
“…In sum, rodent models of sucrose bingeing provide valuable insight into the behavioural and biological underpinnings of maladaptive eating. Restricting access to palatable food increases the propensity to binge, leading to alterations in reward processing (Smail-Crevier et al, 2018) as well as neurophysiological changes associated with compulsive responding (Maracle et al, 2018). We now identify a contribution of MORs to binge eating, findings that may translate to clinical treatment (Ziauddeen et al, 2013).…”
Section: Discussionmentioning
confidence: 75%
“…Functionally, the BNST filters and/or integrates multiple ascending modalities, mapping with adequate resolution, interoceptive information onto motivational systems for adaptive physiological and behavioral outcomes (Jennings et al, 2013; Kim et al, 2013; Lebow and Chen, 2016). Preclinical work compliments studies in humans: we have demonstrated a role for the oval subregion of the BNST (ovBNST) in compulsive behaviors including addiction, compulsive sucrose-seeking, and finally, in SIP (Krawczyk et al, 2013; Gardner Gregory, 2018; Maracle et al, 2019). Accordingly, electrical stimulation of the BNST is reported to suppress SIP in rodents (van Kuyck et al, 2008).…”
Section: The Bed Nucleus Of the Stria Terminalis (Bnst) In Homeostatimentioning
confidence: 82%
“…The ovBNST is ideally organized and connected to regulate diverse motivational states, in part via its synaptic targets [6,[57][58][59][60]. Primarily comprising GABAergic neurons, the BNST can regulate feeding circuits through a monosynaptic GABA projection to the lateral hypothalamus (LH) to suppress glutamatergic neurons and promote feeding [6].…”
Section: Discussionmentioning
confidence: 99%